Application of Fuzzy Logic to Motorcycle Oil Change Cycle with 10W 30 Oil Viscosity - Zata Ismah Sumayyah; Brian Mariano Rahmanto; Muhammad Caesar Hidayat; Nur Ilham Febriansyah; Veto Adi Pertama; Dwi Yulinar Chairunisa; Agung Prayudha Hidayat (Batrisya Education, 2025)
Oil is a fluid that serves to lubricate the engine, so that friction between engine components is relatively small. Oil changes are based on mileage, oil volume, and oil viscosity levels which usually vary depending on the needs of the vehicle's engine. Most riders are often late and do not even know the routine time of oil changes so that the user's motorcycle engine feels damaged. The application of fuzzy logic has become an important approach in modeling the complex and ambiguous system of motorcycle oil change periods with 10W 30 oil viscosity. The purpose of this study is to determine the application of fuzzy logic in determining the optimal oil. exchange interval. Oil is based on factors such as mileage, oil volume, and oil viscosity when viewed from motorcycle use. To represent these variables using fuzzy sets, a fuzzy logic control system was developed that takes into account oil wear and motorcycle operating conditions which was implemented using the mamdani method and calculated using matlab software. The results showed that oil change intervals tailored to operating conditions and the environment can improve engine performance, reduce maintenance costs and extend component life.